Do central country authors of international co-authored publication networks obtain a high research impact? - Tang, Chaoying; Zhang, Guiyang; Naumann, Stefanie E. (Malaysian Journal of Library and Information Science, 2017)
Do central country authors of an international co-authored publication network obtain a high research impact from their international co-authored publications? This study addressed the issue by examining countries’ quantity of scientific publications. We proposed that countries with fewer scientific publications would gain more benefits from their central positions (both degree centrality and betweenness centrality) because their authors’ limited domestic scientific knowledge motivated them to share and access more knowledge during the collaborations. Data from international co-authored publications in the creativity field from 29 countries during 2000-2014 provided support for the hypotheses. Suggestions for international research collaboration policy making are discussed.